PENGARUH MINAT MEMBACA TERHADAP KEAKTIFAN BELAJAR SISWA KELAS VII A PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMP N 03 TELUK KUANTAN - Padila Turahmi; Bustanur Bustanur; Ikrima Mailani (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2019)
This reserch aims to determine the effect of interest in reading towards learning activity of class VII A student in educational subjects Islamic religion (PAI) in SMP N 03 Teluk Kuantan. Using method causal associative and analysis of linear regression data simple. Sampel this researchas many as 24 students, then analyzed the data with provide an explanation of the effects of reading interest on activeness class VII A student learning in Islamic religious education (PAI) in SMP N 03 Teluk Kuantan. Bay based on the result of the field questionnaire that showed the influence of reading interest on the students learning activeness which is significant with the index t hitung is 1.778 and the t tabel 0.001. And the conclusion calculate 1.778 >0.001. Then there is an influence between interest variables reading (X) on activity variables (Y). And determination = 0.126 or 12.6% so the influence of interest in reading on the activity of studying in SMP N 03 Teluk Kuantan range 12.6%.